(untitled) (Conferencea, 2023)
The article is devoted to the problems of optimizing means and loads by adapting and improving junior speed-strength preparedness during the transition to the adult age category in sambo wrestling. To control the level of strength preparedness, running 30 meters, a long jump from a place, throwing a stuff ed ball 3 kg standing back, bending and unbending arms in a resting position, bending and unbending of the lying hands on a low crossbar in a lying leg, lifting the body into gray hair were used lying on the back, dynamometry of the hand, deadweight dynamometry. All methods used were eff ective for the proposed technique in sambo at the stage of sports improvement.